ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN BIREUEN - Nilawati Nilawati; Naz’aina Naz’aina; Muhammad Haykal (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study is an empirical study that aims to analyze the factors that affect the quality of local government financial reports. The type of data used is primary data by distributing questionnaires to all Regional Apparatus Organizations (OPD) of the Bireuen Regency Government, the subject in this study is the LKPD Preparation Team Kab. Bireuen as many as 24 people, Budget Users and Financial Administration Officers as many as 104 people, and Auditors from Bireuen Regency as many as 22 people. The analytical model used in this study is the Partial Least Squard (PLS) analysis using Warppls 7.0. The results showed that the variable Quality of Human Resources had a positive and significant effect on the quality of local government financial reports, Utilization of Information Technology had a significant positive effect on the Quality of Local Government Financial Reports, Regional Financial Accounting Systems had a significant positive effect on the Quality of Local Government Financial Reports, Internal Control Systems has a significant positive effect on the Quality of Local Government Financial Reports, the Internal Control System is able to strengthen the influence of the Quality of Human Resources on the Quality of Local Government Financial Reports, the Internal Control System is not able to strengthen the influence of the use of information technology on the Quality of Local Government Financial Reports, the Internal Control System is not able to strengthen the the influence of the regional financial accounting system on the Quality of Local Government Financial Reports.